The influence Quality of information, Sistem Quality and Service Quality on Satisfaction and User Performace - Isnaeningsih, Heni Nur; Fitriati, Azmi; Pujiharto, Pujiharto; Astuti, Herni Justiana (Jurnal Manajemen Bisnis, 2021)
Research aims: This study aims to analyze the effect of information quality, system quality, and service quality on user satisfaction so that it has an impact on user performance.Design/Methodology/Approach: This type of research is conducted using a quantitative approach, namely research using research instruments, quantitative data analysis with the aim of testing the predetermined hypothesis,The sample used was 61 Religious Teachers at Muhammadiyah Vocational Schools in Cilacap Regency. The data obtained through questionnaires were processed using PLS analysis (Partial Leas Square). Testing the research model (Outer Model) was carried out in two stages, namely testing of the measurement model (Outer Model) with Convergent Validity, Discriminate Validity and structural testing (Inner Model) with Path Coeffecient, Specific Indirect Value.Research findings: The results of data analysis show that information quality has no effect on user satisfaction, system quality, service quality has a positive effect on user satisfaction, system quality has no effect on user performance, service quality affects user performance, information quality, user satisfaction has a positive effect on user performance, namely religion teacher at Muhammadiyah Vocational High School in Cilacap Regency.Theoretical contribution/ Originality: This study examines the influence of information quality, system quality and service quality for employeesPractitioner/Policy implication: it should be that the higher the level of information quality, system quality, service quality, the higher the performanceResearch limitation/Implication: This research was only conducted in Muhammadiyah Junior High School in Cilacap Regency